The Structure and Function of Gut Microbiomes of Two Species of Sea Urchins, Mesocentrotus nudus and Strongylocentrotus intermedius, in Japan - Haditomo, Alfabetian Harjuno Condro; Yonezawa, Masanori; Yu, Juanwen; Mino, Sayaka; Sakai, Yuichi; Sawabe, Tomoo (Frontiers in Marine Science, 2021)
Sea urchin is an indicator of coastal environmental changes in the global warming era, and is also a model organism in developmental biology and evolution. Due to the depletion of wild resources, new aquaculture techniques for improving stocks have been well studied. The gut microbiome shapes various aspects of a host’s physiology. However, these microbiome structures and functions on sea urchins, particularly Mesocentrotus nudus and Strongylocentrotus intermedius which are important marine bioresources commonly found in Japan, have not been fully investigated yet. Using the metagenomic approach, the structures, functions, and dynamics of the gut microbiome of M. nudus and S. intermedius, related to both habitat environment and host growth, were studied. Broad meta16S analysis revealed that at the family level, Psychromonadaceae and Flavobacteriaceae reads (38%-71%) dominated in these sea urchins, which is a unique feature observed in species in Japan. Flavobacteriaceae reads were more abundant in individuals after rearing in an aquarium with circulating compared to one with running water. Campylobacteraceae and Vibrionaceae abundances increased in both kinds of laboratory-reared sea urchins in both types of experiments. Two-weeks feeding experiments of M. nudus and S. intermedius transplanted from the farm to laboratory revealed that these gut microbial structures were affected by diet rather than rearing environments and host species. Further meta16S analysis of microbial reads related to M. nudus growth revealed that at least four ASVs affiliated to Saccharicrinis fermentans, which is known to be a nitrogen fixer, showed a significant positive correlation to the body weight and shell length. Interestingly, gut microbiome comparisons from individuals showing higher and lower growth rates revealed a significant abundance of ‘Nitrate and nitrite ammonification’ genes in the higher-grown individuals. These findings provide new insights on the structure-function relationship of sea urchin gut microbiomes beyond previously reported nitrogen fixation function in sea urchin in 1950s; we discovered a nitrate reduction function into ammonium for the growth promotion of sea urchin.